The Influence of Higher Education Image and Tuition Fees on Students' Decision to Study at the University of Muhammadiyah Pontianak - Samsul; Samsuddin (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2024)
This study uses an associative method to investigate the relationship between the image of higher education and the cost of education on students' decisions in choosing to study at the University of Muhammadiyah Pontianak. Data was collected through interviews, observations, and questionnaires distributed to 100 active students. The results of this study provide a deeper understanding of the factors that influence students' decisions in choosing universities. Therefore, educational institutions need to pay attention to their image and education fee policies to increase their attractiveness in the eyes of prospective students